2008
DOI: 10.1158/1078-0432.ccr-07-0666
|View full text |Cite
|
Sign up to set email alerts
|

Mature miR-184 as Potential Oncogenic microRNA of Squamous Cell Carcinoma of Tongue

Abstract: Purpose: The aim of this study was to evaluate the microRNA expression patterns in squamous cell carcinoma (SCC) of the tongue. Experimental Design: Expression levels of 156 human mature microRNAs were examined using real-time quantitative PCR (Taq Man MicroRNA Assays; Human Panel) on laser microdissected cells of 4 tongue carcinomas and paired normal tissues. Expression of mature miR-184 was further validated in 20 paired tongue SCC and the normal tissues. Potential oncogenic functions of miR-184 were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
608
5
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 699 publications
(664 citation statements)
references
References 12 publications
38
608
5
5
Order By: Relevance
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple microRNAs in miR-106 family and related miRNAs rescue Ras-induced senescence and induce colony formation in soft agar in HMECs via downregulation of p21 by miR-106/302 [28]. They are associated with progression of variable tumors; miR-106a and miR-106b in gastric adenocarcinoma [29], miR-17-5p and miR-372 in squamous cell carcinoma [30], miR-372 and miR-373 in testicular germ cell tumors [10], and miR-373 with miR-520c in the metastatic tumors [31]. Moreover, inactivation of p21 and p16 INK4a facilitates immortalization and anchorage independent growth of mouse fibroblasts [11].…”
Section: Discussionmentioning
confidence: 99%
“…One of the best described microRNAs related to cellular proliferation and apoptosis is micro-RNA-21 (hsa-miR-21). 21 hsa-miR-21 is overexpressed in many cancers, including HNSCC, 22,23 and is associated with a poor prognosis in nonsmall cell lung cancer. 24 Its targets include the tumor suppressors phosphatase and tensin homolog, 25 tropomysin 1, 26 and programmed cell death 4.…”
mentioning
confidence: 99%